Cytomegalovirus infection in patients after orthotopic liver transplantation (clinical report) - D. O. Efremov; O. A. Gerasimova; K. V. Kozlov; I. A. Gabdrakhmanov; K. V. Zhdanov (Журнал инфектологии)
Herpes viruses are widespread in the human population, they are able to infect almost all organs and systems of the body. Currently, 8 serotypes of herpesviruses pathogenic for humans are known: herpes simplex viruses of the 1st and 2nd. type, chickenpox — herpes zoster, cytomegalovirus, Epstein-Barr virus, 6th, 7th and 8th human herpes viruses. Primary infection with herpes viruses in 60—90% of cases occurs in early childhood, and, as a rule, is not accompanied, by typical clinical manifestations. Due to the lack of mandatory registration of the incidence of herpes virus infections in our country, the true number of patients is unknown. It is believed that about 20 million people are infected, every year in Russia and. the CIS countries. Herpes viruses, to a greater or lesser extent, can be considered, hepatotropic. A large number of studies are devoted, to the problem, of cytomegalovirus infection, one of the manifestations of which, is hepatitis. Most often, cytomegalovirus hepatitis occurs in immunocompromised. individuals or in patients receiving immunosuppressive therapy, cases of cytomegalovirus hepatitis and in immunocompetent individuals are also described. With liver transplantation without antiviral therapy, cytomegalovirus infection manifests itself in 11-28,5% of recipients and. can lead, to the development of liver failure, loss of transplant and. death, of the recipient. Performing diagnostic studies using both, serological and. molecular biological methods at different periods after liver transplantation, allows to detect cytomegalovirus infection timely and. initiate treatment, thereby avoiding graft rejection and. the death, of the recipient.